Adaptation and modifications in physical education a special education teachers facilitation - Rubio, Gisella Francisca P. 2000-; Dimarucut, Alberto L. (Quezon City College of Human Kinetics, University of the Philippines Diliman, 2024)
Since there is scant knowledge of PE facilitation of SPED teachers in the country, it is essential to understand how the educators adapt and modify their materials and tasks. However, most SPED teachers still think about what knowledge and skills must be developed to be able to work effectively with students with special needs. It is for this reason that this study this qualitative research study aims to identify the strategies and challenges of SPED teachers when facilitating PE. This study utilized a two-phased operational framework that consists two phases. Phase one is comprised of selection of twenty-two respondents to answer the survey. On the other hand, phase two focused on six SPED teachers from the survey results and went through on one-on-one interview. Systematic Ecological Model for Adapting
Physical Activities (SEMA model) by Hutzler (2007) served as the core framework in creating the contents for these phases. This helped in exploring the various factors of the model: Task, Individual, and Environment. Thematic analysis approach by Braun and Clarke was used to identify patterns across data to derive themes. Results under the factor “Task” revealed the task’s complexity, objectives, equipment, and physical requirement. SPED teachers used a diverse range of specialized tools and resources to support learning and accommodate varying sensory, motor, and communication needs. Moreover, gathered data from the “Individual” discussed why knowing the body’s impairment, function, and motivation are essential in achieving a successful PE class. SPED teachers make assessments and observations to provide a baseline understanding of each student's current abilities, skills, and motivational drive. These are crucial as it directly influences student participation, enjoyment, and long-term engagement in physical activities. Lastly, results regarding the “Environment” showed how accessibility issues, resources, and support are vital in the student’s learning. SPED teachers ensure that they provide appropriate resources in supporting their personalized educational plans in facilitating PE and emphasized how support systems is critical in developing academic, social, and emotional growth within PE classes. In conclusion, the findings found out that SPED teachers perform various ways of adaptations and modifications to achieve a successful facilitation in their PE classes. Modification of materials and tasks showed significance in meeting diverse needs of students. Results also proved that SPED teachers face several challenges when facilitating PE. This includes curriculum, limited resources, student behavior, insufficient specialized training, lack of support, and physical fitness. The researcher recommends an enhanced professional development for the SPED teachers who are facilitating PE. Future studies could advocate on creating a SPED curriculum made by the Philippine government that mandates inclusivity in all aspects of education. PE for students with special needs should be easily available for the Filipinos as much as possible
Thesis (Bachelor of Sports Science) -- University of the Philippines Diliman
Includes bibliographical references
Title in approval sheet different from the title on the cover and title page
Keywords: Physical education and training; Physical education teachers; Special education teachers